Classroom Furniture and Student Body Dimensions in East Malaysian Primary Schools - R.A R.. Ghazilla; Z. Taha; S.H.A. Rashid; Iskandar; Nazaruddin; S.H. Sajeli (Faculty of Psychology, Universitas Surabaya, 2006)
-